2010
DOI: 10.1111/j.1463-1326.2009.01180.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of DSP‐7238, a novel, potent, specific and substrate‐selective DPP IV inhibitor, improves glycaemic control and β‐cell damage in diabetic mice

Abstract: We have shown in this study that DSP-7238 is a potent DPP IV inhibitor that has high specificity for DPP IV and substrate selectivity against GLP-1. We have also found that chronic treatment with DSP-7238 improves glycaemic control and ameliorates beta-cell damage in a mouse model with impaired insulin sensitivity and secretion. These findings indicate that DSP-7238 may be a new therapeutic agent for the treatment of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
(36 reference statements)
3
11
0
1
Order By: Relevance
“…Because the acute study showed that a single oral dose of 3, 10, and 30 mg/kg of SHR117887 in ob/ob mice can only inhibit serum DPP-4 activity by 5.1%, 23.9%, and 52.8%, respectively, at 12 h post-dose, a twice-daily administration was chosen for the chronic study to maintain adequate inhibition of DPP-4 activity throughout the experiment. The dose of 30 mg/kg SHR117887 caused 88.9% and 46.6% inhibition of serum DPP-4 activity at 2 h and 12 h post dose, whereas administration of the same dose of SHR117887 on day 12, 24, and 32 of the chronic treatment exerted almost equivalent DPP-4 inhibition, which indicated that SHR117887 does not exhibit tachyphylaxis when given orally twice daily for 32 d. In agreement with previous stud- [16,20] , SHR117887, significantly decreased fasting blood glucose values and the results were also observed at a comparable level with the same molar dose of LAF237. Moreover, lipid homeostasis was also improved by chronic SHR117887 treatment in ob/ob mice by reducing the serum triglyceride and NEFA levels, which is consistent with the results of previous studies conducted with alogliptin on ob/ob and db/db mice or with a sitagliptin analog (des-fluorositagliptin) in high-fat diet streptozotocin-induced diabetic mice [34][35][36] , suggesting possible beneficial effects of SHR117887 in type 2 diabetic patients associated with lipid dysregulation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Because the acute study showed that a single oral dose of 3, 10, and 30 mg/kg of SHR117887 in ob/ob mice can only inhibit serum DPP-4 activity by 5.1%, 23.9%, and 52.8%, respectively, at 12 h post-dose, a twice-daily administration was chosen for the chronic study to maintain adequate inhibition of DPP-4 activity throughout the experiment. The dose of 30 mg/kg SHR117887 caused 88.9% and 46.6% inhibition of serum DPP-4 activity at 2 h and 12 h post dose, whereas administration of the same dose of SHR117887 on day 12, 24, and 32 of the chronic treatment exerted almost equivalent DPP-4 inhibition, which indicated that SHR117887 does not exhibit tachyphylaxis when given orally twice daily for 32 d. In agreement with previous stud- [16,20] , SHR117887, significantly decreased fasting blood glucose values and the results were also observed at a comparable level with the same molar dose of LAF237. Moreover, lipid homeostasis was also improved by chronic SHR117887 treatment in ob/ob mice by reducing the serum triglyceride and NEFA levels, which is consistent with the results of previous studies conducted with alogliptin on ob/ob and db/db mice or with a sitagliptin analog (des-fluorositagliptin) in high-fat diet streptozotocin-induced diabetic mice [34][35][36] , suggesting possible beneficial effects of SHR117887 in type 2 diabetic patients associated with lipid dysregulation.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have demonstrated the effectiveness of longterm DPP-4 inhibition on amelioration of metabolic disorder in diabetic animal models [20,33] . In the present study, the antidiabetic effects of chronic DPP-4 inhibition by SHR117887 were investigated in ob/ob mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The models used to show improved beta cell function and increased beta cell mass by incretin-based therapy have been genetically deficient rodents, rodents given an exogenous beta cell toxin, and animals with diet-induced obesity (DIO) subsequent to dietary changes introduced at a young age. For example, in many of the studies reporting changes in beta cell mass and function in rodents in response to DPP4 inhibitor treatment, the rodents were either newborn or less than 7 weeks old at the start of the studies and several were treated with the beta cell toxin streptozotocin prior to DPP4 treatment [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…They suggest avoiding sulphonylureas, due to the risk of β-cell exhaustion. DPP-4 inhibitors (gliptins) and biguanides (metformin) may be more reasonable alternatives in view of their specific advantages and adverse effects [156,157]. Alpha-glucosidase inhibitors and thiazolidinediones (TZDs) are not irrational choices, but these agents seem harder to endorse, due to the public debate concerning TZD safety [158] and knowing that many patients will not accept acarbose because of frequent diarrhea and flatulence.…”
Section: Management Of Established Nodatmentioning
confidence: 99%